2010
DOI: 10.4314/nifoj.v25i2.50843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods on antinutrients in selected leafy vegetables

Abstract: The effect of different processing methods on the reduction of selected anti-nutrients in 'Ewuro' (Vernonia amygdalina), 'Igbo' (Solanum macrocarpon), 'Ugwu' (Talferia occidentalis) and 'Utazi' (Marsdenia latifolium) was assessed. The treatments/processing methods used for the assessment were T 1 (Squeezing vegetable with salt and water only), T 2 (Hot water blanching with salt only) T 3 (Squeezing with salt, palm oil and water) and T 4 (Heating with potash and water only). Results obtained indicated significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
6
13
1
Order By: Relevance
“…This is consistent with findings of Adeboye and Babajide, 2007 which revealed lowering effect of heat on saponin content [16]. Juicing, concentrated saponin content of most vegetables observed, though beneficial effect of saponin cannot be over emphasized, however, the intake above recommended dosage might cause deleterious effects such as ferrous complexation and excretion [25] which may affect red blood status, complextion of proteins [26] that may lead to growth depression and also its negative effect on fertility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings of Adeboye and Babajide, 2007 which revealed lowering effect of heat on saponin content [16]. Juicing, concentrated saponin content of most vegetables observed, though beneficial effect of saponin cannot be over emphasized, however, the intake above recommended dosage might cause deleterious effects such as ferrous complexation and excretion [25] which may affect red blood status, complextion of proteins [26] that may lead to growth depression and also its negative effect on fertility.…”
Section: Discussionsupporting
confidence: 91%
“…Also, variation exist in saponin content of different vegetables and are affected by processing methods. [16]. This study revealed variation in saponin content of different vegetables and effect of blanching which reduced saponin content virtually in all the vegetables.…”
Section: Discussionmentioning
confidence: 61%
“…The values obtained in the present study are lower than the lethal dose of 200-500 mg/100g oxalate reported by Bushway et al 29 . Acamovic et al [1][2][3][4][5] , reported 20 g/kg to be lethal to chicken. It has also been reported that the lethal level of oxalate in man is 3-5 g 31 , and that daily intake of 450 mg of oxalic acid interferes with various metabolic processes 8 .…”
Section: Fig 1 : Edible Vegetables Used For the Studymentioning
confidence: 99%
“…Invariably, vegetables present a rich source of vitamins, minerals, fibre and protein. Green leafy vegetables despite their nutritional value are to be consumed with caution because of the presence in them of toxic anti-nutrients [1][2][3][4][5] . Anti-nutrients are natural compounds that interfere with the absorption of nutrients, hence are known to reduce nutrients availability to animals and humans [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…32 Different studies show that the presence of antinutrient components in green leafy vegetables impairs efficient utilization of calcium, zinc, iron, and copper by the formation of insoluble complexes with the mineral elements. 33 Common antinutrients found in vegetables include tannin, hydrocyanic acid, saponins, oxalates, phytates, and polyphenols. 34 Various processing methods, such as soaking, boiling, and frying may help in detoxification of antinutrients and lowers food toxicity.…”
Section: Methods Of Preparationmentioning
confidence: 99%